Climate anomalies associated with the occurrence of rockfalls at high-elevation in the Italian Alps - R. Paranunzio; F. Laio; M. Chiarle; G. Nigrelli; F. Guzzetti (Natural Hazards and Earth System Sciences, 2016)
Climate change is seriously affecting the cryosphere in terms, for example, of permafrost thaw, alteration of rain ∕ snow ratio, and glacier shrinkage. There is concern about the increasing number of rockfalls at high elevation in the last decades. Nevertheless, the exact role of climate parameters in slope instability at high elevation has not been fully explored yet. In this paper, we investigate 41 rockfalls listed in different sources (newspapers, technical reports, and CNR IRPI archive) in the elevation range 1500–4200 m a.s.l. in the Italian Alps between 1997 and 2013 in the absence of an evident trigger. We apply and improve an existing data-based statistical approach to detect the anomalies of climate parameters (temperature and precipitation) associated with rockfall occurrences. The identified climate anomalies have been related to the spatiotemporal distribution of the events. Rockfalls occurred in association with significant temperature anomalies in 83 % of our case studies. Temperature represents a key factor contributing to slope failure occurrence in different ways. As expected, warm temperatures accelerate snowmelt and permafrost thaw; however, surprisingly, negative anomalies are also often associated with slope failures. Interestingly, different regional patterns emerge from the data: higher-than-average temperatures are often associated with rockfalls in the Western Alps, while in the Eastern Alps slope failures are mainly associated with colder-than-average temperatures.